Endovascular and percutaneous transabdominal embolisation of pseudoaneurysms in pancreatitis: an experience from a tertiary-care referral centre. Issue 4 (April 2021) - Gorsi, U.; Agarwal, V.; Nair, V.; Kang, M.; Kalra, N.; Sreedhara, B.C.; Gupta, R.; Rana, S.S.; Dutta, U.; Sandhu, M.S.
Abstract : AIM: To analyse the technical challenges, clinical success, and associated complications of endovascular and percutaneous embolisation of pancreatitis-related pseudoaneurysms. MATERIALS AND METHODS: A retrospective study of patients referred for embolisation of pancreatitis-related pseudoaneurysms between January 2014 and March 2019 was conducted. Computed tomography angiography (CTA) was performed to assess the morphology of the aneurysms prior to any intervention. Percutaneous or endovascular embolisation was performed. Details of CTA and methods of embolisation were recorded. Technical success, clinical success, and complications were reported. RESULTS: A total of 80 patients (mean age, 40.69 ± 13.41 years, 73 male) underwent embolisation during the study period. Pseudoaneurysms were related to chronic pancreatitis (CP) in 44 (55%) patients and acute pancreatitis (AP) in 36 (45%) patients. Pseudoaneurysms were detected in 65 (81.2%) patients on CTA. The most common site of pseudoaneurysms was gastroduodenal artery (GDA) followed by splenic artery. Seven patients were treated with percutaneous thrombin injection and five were treated with percutaneous glue injection under ultrasound/fluoroscopy guidance. The remaining patients ( n= 68) underwent catheter angiography with endovascular embolisation. Technical success was achieved in 4/7 (57%) percutaneous thrombin cases and in all the cases (5/5, 100%) with percutaneous glue or endovascular (68/68, 100%) embolisation. CONCLUSION: Endovascular or percutaneous embolisation of pseudoaneurysms has high technical success with an excellent safety profile. Highlights: Vascular complications are common and life threatening in patients with pancreatitis. Endovascular embolisation of pseudoaneurysms remains the mainstay of treatment. Direct percutaneous embolisation can be performed safely in selective patients. Re bleeding rates are low and most of them occur in first 6 months.